Four Concert Miniatures for Violin and Piano = Štiri koncertne miniature za violino in klavir - Riedling, Oskar (ZRC SAZU, Založba ZRC, 2022)
This edition contains Four Concert Miniatures for Violin and Piano by Oskar Rieding (1846-1916), composed in Celje, shortly before World War I. Although Rieding's compositions have been an important part of the violin repertoire for decades and have appeared in various reprints by major European publishers, Four Concert Miniatures for Violin and Piano has been overlooked until now. These four musically delightful miniatures form a longer, self-rounded cycle with the movements Tendresse (Tenderness), L'Aveu (Confession), Le Départ (Departure), and Désir ardent (Desire). The composer succeeded in capturing an affectionate ambience through the violin cantilena. In these distinctly lyrical character pieces, he expressed romantic feelings with his emblematic melodic style. The present edition fills the knowledge gap about this composer who was active in Celje, but also enriches the violin repertoire intended for advanced performers.